Coordination‐Resolved Spectrometrics of Local Bonding and Electronic Dynamics of Au Atomic Clusters, Solid Skins, and Oxidized Foils. Issue 10 (27th April 2015) - Yu, Wang; Bo, Maolin; Huang, Yongli; Wang, Yan; Li, Can; Sun, Chang Q.
Abstract By using combination of bond‐order–length–strength (BOLS) correlation, the tight‐binding (TB) approach, and zone‐selective photoelectron spectroscopy (ZPS), we were able to resolve local bond relaxation and the associated 4f7/2 core‐level shift of Au atomic clusters, Au(100, 110, 111) skins, and Au foils exposed to ozone for different lengths of time. In addition to quantitative information, such as local bond length, bond energy, binding‐energy density, and atomic cohesive energy, the results confirm our predictions that bond‐order deficiency shortens and stiffens the bond between undercoordinated atoms, which results in local densification and quantum entrapment of bonding electrons. The entrapment perturbs the Hamiltonian, and hence, shifts the core‐level energy accordingly. ZPS also confirms that oxidation enhances the effect of atomic undercoordination on the positive 4f7/2 energy shift, with the associated valence electron polarization contributing to the catalytic ability of undercoordinated Au atoms.